Potensi Siswa dan Kebijakan Pelayanan Bimbingan Konseling (Studi Kasus terhadap Siswa Komunitas Adat Terpencil Suku Sakai di SMAN 1 Kecamatan Pinggir Kabupaten Bengkalis) - Tohirin Tohirin (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
This study aims to uncover the potential students and guidance counseling services policy to students of communities of remote indigenous Sakai tribe at SMAN 1 Bengkalis. During this time students of communities of remote indigenous Sakai tribe portrayed as individuals who do not have superior potency, as well as the traditional left behind and isolated in various aspects of life. This study attempted to uncover the potential of what is owned by the student of communities of remote indigenous Sakai tribe and counseling service policies against them. Through research with qualitative approach (case studies) and observational data collection and interviews revealed that students KAT Sakai tribe also has superior potential, both academic and nonacademic. Students of communities of remote indigenous Sakai tribe there who became an ambassador for the school to follow the science olympiad in Pekanbaru. LB policy service delivery to students of communities of remote indigenous Sakai tribe is not solely the principal’s initiative, but government policies that should be realized in the school. Service objectives are to help solve the problems they face. BK care given to approach the crisis in which new students are given the service when they are in trouble. The main obstacle in SMAN 1 Bengkalis. Edge comes from the students themselves of communities of remote indigenous Sakai tribe.